Comparação dos caldos selenito cistina, tetrationato Muller-Kauffmann e Rappaport-Vassiliadis no isolamento de Salmonella Typhimurium - Ávila, L.G.; Silva, D.G; Fagliari, J.J. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2012)
Three selective enrichment broths - selenite cystine (SC), Muller-Kauffmann tetrathionate (MKT) and Rappaport-Vassiliadis (RV) - were compared, for Salmonella Typhimurium isolation from rectal swabs of a calf experimentally infected. The bacteriological procedure involved pre-enrichment in Hajna-GN broth (only for the samples inoculated in RV broth), selective enrichment (SC, MKT and RV broths), culture in modified brilliant green agar (BGA), presumptive biochemistry tests (using triple-sugar-iron agar and lysine-agar) and slide agglutination test with poli-O and poli-H Salmonella antisera. SC and MKT broths were more efficient in the isolation of Salmonella Typhimurium (12 positive samples), whereas RV broth had a lower efficiency in the microbiological isolation (ten positive samples).
Comparison of selenite cystine, tetrathionate Muller-Kauffmann and Rappaport-Vassiliadis broths for Salmonella Typhimurium isolation
Keywords: Calves; feces; selective enrichment broth; Salmonella Typhimurium; bezerro; fezes; meio de enriquecimento seletivo; Salmonella Typhimurium